1973
DOI: 10.1136/jmg.10.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Origin of 48,XXXY: The Evidence of the Xg Blood Groups

Abstract: Summary. A third family is reported in which the Xg groups give information about the origin of an XXXY member: successive non-disjunction at the first and second paternal meiotic divisions is much the most likely cause. In the two previous informative families successive non-disjunction at maternal meiotic divisions was the most likely cause. An enquiry showed the average age of 29 fathers at the birth of XXXY sons to be 32-41 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Rinaldi et al (1979) demonstrated paternal nondisjunction in a single patient with 48,XXYY karyotype. But in two of five reported cases of 48,XXXY, maternal nondisjunction was deduced ; Greenstein et al 1970;Sanger et al 1971;Pfeiffer and Sanger 1973;Lorda-S~nchez et al 1992). In our study all tetrasomies (both 48,XXYY and 48,XXXY) were from paternal origin (see Table 1).…”
Section: Resultsmentioning
confidence: 92%
“…Rinaldi et al (1979) demonstrated paternal nondisjunction in a single patient with 48,XXYY karyotype. But in two of five reported cases of 48,XXXY, maternal nondisjunction was deduced ; Greenstein et al 1970;Sanger et al 1971;Pfeiffer and Sanger 1973;Lorda-S~nchez et al 1992). In our study all tetrasomies (both 48,XXYY and 48,XXXY) were from paternal origin (see Table 1).…”
Section: Resultsmentioning
confidence: 92%